Enhanced Field Emission Performance of MoO3 Nanorods and MoO3‐rGO Nanocomposite. Issue 33 (29th November 2017) - Bankar, Prashant K.; Khandare, Lina N.; Late, Dattatray J.; More, Mahendra A.
Abstract: The graphene and semiconducting hybrid based nanostructures have emerged as a new class of multifunctional materials with improved performance in comparison to the pristine semiconductors. Here, as‐synthesized MoO3 ‐reduced graphene oxide (rGO) nanocomposite emitter exhibits enhanced field emission (FE) behavior as compared to the pristine 1D MoO3 nanorods. The hydrothermally synthesized 1D MoO3 nanorods (1D) are grafted on the rGO sheet (2D) using a simple room temperature sonochemical method. The morphological and structural analysis confirms the attachment of MoO3 nanorods with rGO and the improved conductivity of the sample indicates a strong electronic interaction between them. Furthermore, the FE studies of as‐synthesized MoO3 nanorods and MoO3 ‐rGO nanocomposite emitters, carried out at a base pressure ∼1×10 −8 mbar, reveals the values of turn on field (required to draw an emission current density of 1 μA/cm 2 ) as 1.6 and 1.4 V/μm, respectively. Interestingly, the maximum emission current density of 2810 μA/cm 2 is achieved at a lower applied field of 2.7 V/μm from the MoO3 ‐rGO nanocomposite emitter. The enhancement in FE performance of MoO3 ‐rGO nanocomposite is attributed to the improved electrical conductivity, mechanical properties and higher concentration of protruding edges (emission sites). This observation can be extended to other graphene‐based 1D inorganic hybrid semiconductor nanocomposites, which can provide a valuable opportunity to explore novel hybrid materials for vacuum nano‐electronic devices. Abstract : The MoO3 ‐rGO nanocomposite exhibits superior field emission envisaged as lower turn‐on and threshold fields, along with very high emission current density of 2810 μA/cm 2 at relatively lower applied field of 2.7 V/μm. The promising FE behavior of the MoO3 ‐rGO nanocomposite emitter has been attributed to synergic effect of improved electrical properties and presence of more number of emission sites.